Low nutrient losses by deep leaching after clearcutting and replanting Eucalyptus plantations in Brazil - Caldeira, Alberto [UNESP]; Krushe, Alex Vladimir; Mareschal, Louis; da Silva, Paulo; Nouvellon, Yann; Campoe, Otavio; Luiz Stape, Jose [UNESP]; Montebelo, Alexandra; Formaglio, Greta; le Maire, Guerric; Guillemot, Joannès; Ranger, Jacques; et al. (Elsevier, 2023)
Sustainable management of highly productive eucalypt plantations requires the application of fertilizers to balance nutrient exports associated with biomass removal every 6-7 years. Although deep leaching after clear-cutting is an important component of input-output budgets of nutrients in forest soils, accurate quantifications are rare in tropical plantations. Our study aimed to assess the consequences of management practices in highly productive eucalypt plantations on nutrient losses by deep leaching in two hillslope positions with contrasting soil types. Soil solutions were continuously collected using lysimeters down to a depth of 3 m, in the last year before the clear-cutting, then in the first 3.5 years after replanting. Concentrations of the main cations and anions were determined monthly and fluxes of gravitational solutions at the depths where the lysimeters were installed were estimated using the Hydrus 1D model, calibrated in situ. Stand productivity was high in both landscape positions with a mean basal area at harvest of 35 m2 ha-1 at the bottom of the slope and 27 m2 ha-1 at the top of the slope. Soil solution chemistry in the topsoil was highly responsive to management practices with sharp increases in ionic charges after clearcutting and fertilizer applications. While leaching fluxes of mobile ions (especially N-NO3-, K+ and Mg2+) reached values greater than 30 kg ha-1 yr-1 at a depth of 1 m after clear-cutting, they remained lower than 3 kg ha-1 yr-1 at a depth of 3 m both in the upper and lower hillslope positions throughout the rotation. Our study suggests that splitting fertilizer applications may not be necessary in tropical Eucalyptus plantations established in very deep tropical soils.
Keywords: Biogeochemical cycles; Brazil; Deep drainage; Dissolved nutrients; Fertilization; Forest management; Silviculture; Soil solution